Lithium cobalt oxide positive electrode material with composite phase as well as preparation method and application of lithium cobalt oxide positive electrode material
By regulating the composite proportion of lithium cobalt oxide positive electrode material and introducing M1 doping, the rate performance and high voltage structural stability of the material are optimized, and the problem of insufficient battery life of traditional lithium cobalt oxide materials in high-power consumption equipment is solved, and the problem of insufficient battery life in high-power consumption equipment is realized. High energy density and high stability battery performance.
Patent Information
- Application Number
- CN202411486181.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Traditional lithium cobalt oxide cathode materials have poor rate performance, poor cycling stability at high voltages and low specific capacity, resulting in insufficient battery life in high power consumption equipment.
By regulating the composite phase ratio of lithium cobalt oxide positive electrode material, a composite structure with O2 phase, T2 phase and O3 phase was prepared. Combined with M1 doping, the rate performance, high voltage structural stability and thermodynamic stability of the material are optimized.
The lithium cobalt oxide cathode material with high energy density and high stability is achieved, which improves the rate performance of the material, cycle stability and structural stability at high voltages, and extends the service life of the battery.
Smart Images

Figure CN119153682A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a lithium cobalt oxide positive electrode material with a composite phase, and a preparation method and application thereof. Background Art
[0002] In portable electronic devices, electric vehicles and energy storage systems, lithium-ion batteries have high energy density, long cycle life and good safety performance, making them the preferred solution for power supply. However, with the development of intelligent devices, their high power consumption computing power has put forward higher requirements for battery life. Therefore, the development of high energy density lithium-ion battery positive electrode materials is a key factor in promoting its further development.
[0003] Traditional lithium cobalt oxide positive electrode materials are O3 phase structures and belong to the R-3m space group. Thanks to its advantages such as high compaction density and high energy density, it is widely used in energy storage fields such as 3C electronic devices. In actual use, the diffusion path of lithium ions in the bulk phase of lithium cobalt oxide with an O3 phase structure is single, and is affected by the electrostatic repulsion of the layer transition metal elements, which makes its diffusion rate relatively slow, ultimately resulting in poor rate performance of O3 phase lithium cobalt oxide. In addition, when charged to a high voltage (greater than 4.5V), a large number of lithium ions in the lithium cobalt oxide with an O3 phase structure will escape from the bulk structure, which will lead to an irreversible phase change in the crystal structure and generate electrochemically inert Co on its surface. 3 O 4 , which will cause the surface lithium ion conduction to be blocked and the capacity to be irreversibly decayed.
[0004] In summary, the current traditional lithium cobalt oxide cathode materials have problems such as poor rate performance, poor cycle stability under high voltage, and low specific capacity. Therefore, there is an urgent need to seek a lithium-ion battery cathode material with high specific capacity, high voltage platform, good structural reversibility, and stable structure under high voltage. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium cobalt oxide positive electrode material with a composite phase and a preparation method and application thereof in view of the defects in the prior art. By regulating the composite phase ratio of the lithium cobalt oxide positive electrode material, the rate performance, structural stability under high voltage, thermodynamic structural stability, specific capacity and discharge platform of the positive electrode material can be effectively improved, thereby realizing a lithium cobalt oxide positive electrode material with both high energy density and high stability.
[0006] To achieve the above object, the present invention provides a lithium cobalt oxide positive electrode material with a composite phase, the chemical formula of which is A X Co 1-y M1 y O 2 ;
[0007] Wherein, 0.5≤x≤1, 0≤y≤0.03, A is Li or Li and Na, and M1 is one or more of Al, Zr, Ni, Mn, Y, Nb, La, Fe, Cu, Cr, Ti, W, Mg, Mo or Yb;
[0008] The composite phase of the lithium cobalt oxide positive electrode material includes an O2 phase, a T2 phase and an O3 phase; wherein the sum of the molar proportions of the O2 phase and the T2 phase in the composite phase is greater than or equal to 90%, and the molar proportion of the O3 phase is greater than 0 and less than or equal to 10%.
[0009] Preferably, the chemical formula of the lithium cobalt oxide positive electrode material having a composite phase is Li x1 Na X2 Co 1-y M1 y O 2 , 0.5<x1<0.996, 0.0001≤x2≤0.004, 0≤y≤0.03, M1 is at least one of Al, Mg, and Ti.
[0010] Preferably, the molar ratio of the O2 phase in the composite phase is 1%-65%, the molar ratio of the T2 phase in the composite phase is 25%-98%, and the molar ratio of the O3 phase in the composite phase is 1%-10%.
[0011] Further preferably, the O2 phase, the T2 phase and the O3 phase are evenly or unevenly distributed in the bulk structure of the lithium cobalt oxide positive electrode material;
[0012] The molar ratio of the O2 phase in the composite phase is 40%-65%, the molar ratio of the T2 phase in the composite phase is 30%-55%, and the molar ratio of the O3 phase in the composite phase is 5%-10%.
[0013] Preferably, M1 is evenly distributed or gradiently distributed in the bulk phase of the lithium cobalt oxide positive electrode material having a composite phase.
[0014] Preferably, the lithium cobalt oxide of the T2 phase structure has a characteristic peak corresponding to the (002) crystal plane in the range of 17.00°≤2θ≤18.08°, a characteristic peak corresponding to the (112) crystal plane in the range of 40.7°≤2θ≤42.2°, and a characteristic peak corresponding to the (114) crystal plane in the range of 52.1°≤2θ≤53.9°;
[0015] Lithium cobalt oxide with O2 phase structure has a characteristic peak corresponding to the (002) crystal plane in the range of 18.08°<2θ≤18.32°, a characteristic peak corresponding to the (102) crystal plane in the range of 36.2°≤2θ≤37.7°, and a characteristic peak corresponding to the (105) crystal plane in the range of 56.7°≤2θ≤57.9°;
[0016] Lithium cobalt oxide with O3 phase structure has a characteristic peak corresponding to the (003) crystal plane in the range of 18.51°≤2θ≤19.72°, and a characteristic peak corresponding to the (104) crystal plane in the range of 45.1°≤2θ≤45.9°;
[0017] Among them, the characteristic peak intensity of the T2 phase structure corresponding to the (002) crystal plane in the range of 17.00°≤2θ≤18.08° is I1, the characteristic peak intensity of the O2 phase structure corresponding to the (002) crystal plane in the range of 18.08°<2θ≤18.32° is I2, and the characteristic peak intensity of the O3 phase structure corresponding to the (003) crystal plane in the range of 18.51°≤2θ≤19.72° is I3, I1, I2, and I3 satisfy 0.5≤I2 / I1≤1.5, 0.1≤I3 / I2≤0.8; preferably, 0.8≤I2 / I1≤1.1, 0.2≤I3 / I2≤0.5.
[0018] Preferably, the lithium cobalt oxide positive electrode material having a composite phase is a spherical particle composed of primary particles and / or secondary particles;
[0019] The primary particles are composed of one or more crystal grains, the primary particles are flaky in shape, and have an average particle size of 4 μm-50 μm, preferably 5 μm-30 μm; the secondary particles are composed of agglomerates of multiple primary particles.
[0020] In a second aspect, an embodiment of the present invention provides a method for preparing the lithium cobalt oxide positive electrode material having a composite phase as described in the first aspect, comprising:
[0021] The sodium source and the cobalt source doped or not doped with the M1 element are weighed, mixed, and first sintered according to a stoichiometric ratio to obtain a P2 phase sodium cobaltate material; wherein the molar ratio of sodium in the sodium source to cobalt in the cobalt source is greater than or equal to 0.8; the first sintering has a heating rate of 3-20°C / min, a sintering temperature of 700-1000°C, and a sintering time of 10-36 hours;
[0022] The P2 phase sodium cobalt oxide material is mixed with a lithium source in a molar ratio of n(Na):n(Li)=1:1.5-1:10, and a second sintering is performed in an air atmosphere or an oxygen atmosphere to carry out a molten salt ion exchange reaction, and the second sintered product is washed with water to obtain a lithium cobalt oxide positive electrode material with a composite phase; wherein the heating rate of the second sintering is 3-20°C / min, the sintering temperature is 250°C to 300°C, and the sintering time is 12-36 hours.
[0023] Preferably, the cobalt source includes: one or more of cobalt tetroxide, cobalt hydroxide, cobalt chloride, cobalt acetate, cobalt sulfate, and cobalt nitrate;
[0024] The sodium source includes: one or more of sodium carbonate, sodium hydroxide, sodium chloride, sodium nitrate, and sodium sulfate;
[0025] M1 is one or more of Al, Zr, Ni, Mn, Y, Nb, La, Fe, Cu, Cr, Ti, W, Mg, Mo or Yb;
[0026] The weighing according to the stoichiometric ratio is specifically: weighing according to the molar ratio of Na, Co, and M1 being [0.8-1]: [0.97-1]: [0-0.03];
[0027] The lithium source includes: one or more of lithium hydroxide, lithium nitrate, lithium chloride, lithium bromide, lithium sulfate, and lithium carbonate;
[0028] The heating rate of the second sintering is 3-15°C / min, the sintering temperature is 255°C-265°C, and the sintering time is 12-14 hours.
[0029] In a third aspect, an embodiment of the present invention provides a lithium battery, comprising the lithium cobalt oxide positive electrode material with a composite phase as described in the first aspect above, or comprising the lithium cobalt oxide positive electrode material with a composite phase prepared by the preparation method as described in the second aspect above;
[0030] The lithium battery includes any one of a liquid lithium ion battery, a liquid metal lithium battery, a hybrid solid-liquid lithium ion battery, a hybrid solid-liquid metal lithium battery, a solid lithium ion battery or a solid metal lithium battery.
[0031] The lithium cobalt oxide positive electrode material with a composite phase provided by an embodiment of the present invention has a composite phase structure of an O2 phase, a T2 phase and an O3 phase. The sum of the molar proportions of the O2 phase and the T2 phase in the composite phase is greater than or equal to 90%. The lithium cobalt oxide with an O2 phase structure has excellent rate performance, and the unique lithium oxygen tetrahedral configuration of the lithium cobalt oxide with a T2 phase structure improves the structural stability of the lithium cobalt oxide material at high voltage, so that the lithium cobalt oxide positive electrode material can have both excellent rate performance and high voltage cycle stability. In addition, during the charging process of the lithium cobalt oxide positive electrode material, the O2 phase structure will also be transformed into a T2 phase lithium cobalt oxide with a Cmca crystal structure, so that there is enough lithium oxygen tetrahedral configuration between the layers as an interlayer "pillar support", which can further greatly improve the structural stability of the lithium cobalt oxide at high voltage, and ensure that the composite phase lithium cobalt oxide material has excellent high voltage stability. The composite phase also contains an O3 phase with a molar proportion of less than or equal to 10%, which can improve the overall discharge platform and energy density of the positive electrode material. Furthermore, by introducing M1 doping, the cycle stability of the lithium cobalt oxide positive electrode material can be further improved. At the same time, the irreversible structural phase change and surface structure reconstruction of the positive electrode material under high voltage can be inhibited, thereby further improving the electrochemical performance of the positive electrode material under high voltage.
[0032] The lithium cobalt oxide positive electrode material with a composite phase proposed in the present invention can effectively improve the rate performance, structural stability under high voltage, thermodynamic structural stability, specific capacity, discharge platform and other characteristics of the positive electrode material, thereby realizing a lithium cobalt oxide positive electrode material with both high energy density and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 An X-ray diffraction (XRD) diagram of a lithium cobalt oxide positive electrode material having a composite phase provided in Example 2 of the present invention;
[0034] Figure 2 XRD diagram of the lithium cobalt oxide positive electrode material with a composite phase provided in Example 3 of the present invention;
[0035] Figure 3 XRD diagram of the lithium cobalt oxide positive electrode material with a composite phase provided in Comparative Example 1 of the present invention;
[0036] Figure 4 XRD diagram of the lithium cobalt oxide positive electrode material with a composite phase provided in Comparative Example 2 of the present invention;
[0037] Figure 5 XRD diagram of pure phase lithium cobalt oxide positive electrode materials provided in Comparative Examples 3 and 4 of the present invention;
[0038] Figure 6 A scanning electron microscope (SEM) image of a lithium cobalt oxide positive electrode material having a composite phase provided in Example 1 of the present invention;
[0039] Figure 7 This is a SEM image of a lithium cobalt oxide positive electrode material having a composite phase provided in Example 2 of the present invention;
[0040] Figure 8 This is a SEM image of a lithium cobalt oxide positive electrode material having a composite phase provided in Example 3 of the present invention;
[0041] Fig. 9 This is a SEM image of a lithium cobalt oxide positive electrode material having a composite phase provided in Example 4 of the present invention;
[0042] Fig.10 This is a SEM image of the lithium cobalt oxide positive electrode material with a composite phase provided in Comparative Example 1 of the present invention;
[0043] Fig.11 This is a SEM image of a lithium cobalt oxide positive electrode material with a composite phase provided in Comparative Example 2 of the present invention;
[0044] Fig.12 This is a SEM image of the pure phase lithium cobalt oxide positive electrode material provided in Comparative Example 3 of the present invention;
[0045] Fig.13 This is a SEM image of the pure phase lithium cobalt oxide positive electrode material provided in Comparative Example 4 of the present invention;
[0046] Fig.14 This is a charge and discharge cycle curve diagram of Example 1 of the present invention;
[0047] Fig.15 This is a charge and discharge cycle curve diagram of Example 2 of the present invention;
[0048] Fig.16 This is a charge and discharge cycle curve diagram of Example 3 of the present invention;
[0049] Fig.17 This is a charge and discharge cycle curve diagram of Example 4 of the present invention;
[0050] Fig.18 It is a charge and discharge cycle curve diagram of comparative example 1 of the present invention;
[0051] Fig.19 The charge and discharge cycle curve diagram of Comparative Example 2 of the present invention;
[0052] Fig. 20 It is a charge and discharge cycle curve diagram of comparative example 3 of the present invention;
[0053] Fig.21 It is a charge and discharge cycle curve diagram of comparative example 4 of the present invention;
[0054] Fig. 22 This is a comparison chart of the energy density of lithium-ion batteries assembled from the positive electrode materials of Examples 2-3 and Comparative Examples 1-4 after 100 cycles at a current density of 0.5C;
[0055] Fig.23 The figure is a rate performance diagram of lithium-ion batteries assembled from the positive electrode materials of Examples 1-4 and Comparative Examples 1-4 at current densities of 0.1C, 0.5C, 1C, 2C, 3C, and 5C. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0057] The present invention provides a lithium cobalt oxide positive electrode material with a composite phase, the chemical formula of which is A X Co 1- y M1 y O 2 ; Wherein, 0.5≤x≤1, 0≤y≤0.03, A is Li or Li and Na, and M1 is one or more of Al, Zr, Ni, Mn, Y, Nb, La, Fe, Cu, Cr, Ti, W, Mg, Mo or Yb;
[0058] In the case where A is Li and Na, the chemical formula of the lithium cobalt oxide positive electrode material having a composite phase is Li x1 Na X2 Co 1- y M1 y O 2 , 0.5<x1<0.996, 0.0001≤x2≤0.004, 0≤y≤0.03. In the case where lithium cobalt oxide contains a small amount of Na ions, the presence of Na ions will make the interlayer spacing of lithium cobalt oxide larger, which is conducive to storing more Li and facilitating the rapid diffusion of Li ions. In addition, the presence of Na ions can also serve as interlayer pillars (also called intercalation pillars, pilling) to prevent the collapse of the layered structure, which can stabilize the positive electrode layered structure in the system and improve the cycle performance of the material. x1, x2, and y can be any value within the above range, for example, x1 can be 0.6, 0.7, 0.8, 0.9, 0.995; x2 can be 0.0001, 0.0005, 0.001, 0.002, 0.003, 0.004; y can be 0, 0.001, 0.002, 0.005, 0.007, 0.01, 0.02, 0.03, but are not limited to the above values.
[0059] When y≠0, M1 exists in the bulk phase of the lithium cobalt oxide positive electrode material with a composite phase, and is uniformly distributed or gradient distributed. The gradient distribution is that the M1 content gradually increases from the inside to the outside, which can be specifically regulated by the sintering temperature and time in the preparation. Within the process range, the higher the temperature and the longer the time, the more uniform the distribution of M1 obtained. M1 is preferably at least one of Al, Mg, and Ti. Introducing a small amount of doping element M1 into the system can inhibit the irreversible phase change and surface structure reconstruction of the positive electrode material at high voltage, thereby further improving the electrochemical performance of the positive electrode material at high voltage and improving the cycle stability of the lithium cobalt oxide positive electrode material.
[0060] The composite phase of the lithium cobalt oxide positive electrode material includes an O2 phase, a T2 phase and an O3 phase; wherein the sum of the molar proportions of the O2 phase and the T2 phase in the composite phase is greater than or equal to 90%, and can be any value within the above range, such as 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, but not limited to the above values. The molar proportion of the O3 phase is greater than 0 and less than or equal to 10%, and can be any value within the above range, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, but not limited to the above values. The O2 phase, the T2 phase and the O3 phase are evenly or unevenly distributed in the bulk structure of the lithium cobalt oxide positive electrode material.
[0061] Preferably, the molar ratio of the O2 phase in the composite phase is 1%-65%, the molar ratio of the T2 phase in the composite phase is 25%-98%, and the molar ratio of the O3 phase in the composite phase is 1%-10%. More preferably, the molar ratio of the O2 phase in the composite phase is 40%-65%, the molar ratio of the T2 phase in the composite phase is 30%-55%, and the molar ratio of the O3 phase in the composite phase is 5%-10%.
[0062] The lithium cobalt oxide positive electrode material with a composite phase of the present invention is a spherical particle, which is composed of primary particles and / or secondary particles; wherein the primary particles are composed of one or more crystal grains, the morphology of the primary particles is flaky, and the average particle size is 4μm-50μm, such as 4μm, 6μm, 8μm, 10μm, 20μm, 30μm, 40μm, 50μm, but is not limited to the listed values, and can be any value within the above range. Preferably, it is 5μm-30μm. The secondary particles are composed of a plurality of primary particles agglomerated.
[0063] The lithium cobalt oxide positive electrode material with a composite phase of the present invention meets the following characteristics:
[0064] Lithium cobalt oxide with T2 phase structure has a characteristic peak corresponding to the (002) crystal plane in the range of 17.00°≤2θ≤18.08°, a characteristic peak corresponding to the (112) crystal plane in the range of 40.7°≤2θ≤42.2°, and a characteristic peak corresponding to the (114) crystal plane in the range of 52.1°≤2θ≤53.9°;
[0065] Lithium cobalt oxide with O2 phase structure has a characteristic peak corresponding to the (002) crystal plane in the range of 18.08°<2θ≤18.32°, a characteristic peak corresponding to the (102) crystal plane in the range of 36.2°≤2θ≤37.7°, and a characteristic peak corresponding to the (105) crystal plane in the range of 56.7°≤2θ≤57.9°;
[0066] Lithium cobalt oxide with O3 phase structure has a characteristic peak corresponding to the (003) crystal plane in the range of 18.51°≤2θ≤19.72°, and a characteristic peak corresponding to the (104) crystal plane in the range of 45.1°≤2θ≤45.9°;
[0067] Among them, the characteristic peak intensity of the T2 phase structure corresponding to the (002) crystal plane in the range of 17.00°≤2θ≤18.08° is I1, the characteristic peak intensity of the O2 phase structure corresponding to the (002) crystal plane in the range of 18.08°<2θ≤18.32° is I2, and the characteristic peak intensity of the O3 phase structure corresponding to the (003) crystal plane in the range of 18.51°≤2θ≤19.72° is I3, I1, I2, and I3 satisfy 0.5≤I2 / I1≤1.5, 0.1≤I3 / I2≤0.8; preferably, 0.8≤I2 / I1≤1.1, 0.2≤I3 / I2≤0.5.
[0068] The space group of the O2 phase structure is P63mc, and the space group of the T2 phase structure is Cmca. Since the lithium cobalt oxide of the O2 phase (P63mc space group) structure has a unique layer stacking structure, the diffusion path of lithium ions in the positive electrode material layer is diversified and the diffusion energy barrier is small. The main phase structure of the composite phase of the present invention contains the O2 phase, which can enrich the ion diffusion channel in the bulk structure of the lithium cobalt oxide, which is beneficial to improve the diffusion kinetics of lithium ions in the positive electrode material structure, and thus has excellent rate performance. The unique lithium oxygen tetrahedral configuration in the T2 phase structure can improve the structural stability of the material at high voltage. Although the rate performance of the O2 phase lithium cobalt oxide is excellent and the specific capacity of the pure phase lithium cobalt oxide is high, the discharge platform of the O2 phase lithium cobalt oxide with relatively poor thermodynamic stability is low, which leads to the low energy density of the O2 phase lithium cobalt oxide compared with the O3 phase lithium cobalt oxide with better thermodynamic stability, which limits the application of the O2 phase lithium cobalt oxide to a certain extent. The present invention uses O2 phase and T2 phase as the main phase structure of the lithium cobalt oxide positive electrode material to simultaneously obtain good cycle stability and rate performance. This is because when the lithium cobalt oxide material of the present invention is charged to a high voltage of 4.6V, the O2 phase will further transform into the T2 phase, which can not only improve the structural stability of the lithium cobalt oxide positive electrode material at a high charging voltage, but also unexpectedly increase the interlayer spacing of the lithium cobalt oxide material, so that the lithium cobalt oxide positive electrode material of the present invention has a high rate performance. The total content of the O2 phase and the T2 phase in the composite phase in the lithium cobalt oxide positive electrode material of the present invention and the ratio of their respective contents are limited within the scope of the present invention, which can synergistically exert the advantages of the two, so that the lithium cobalt oxide positive electrode material can have both excellent rate performance and high voltage cycle stability. The composite phase of the lithium cobalt oxide positive electrode material of the present invention also contains an O3 phase, the space group of the O3 structural phase is R-3m, and the molar ratio of the O3 phase is greater than 0 and less than or equal to 10 mol%, and the specific value can be 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, but not limited to this. The molar ratio of the O3 phase is preferably greater than or equal to 5 mol%. The O3 phase itself is a thermodynamically stable phase structure. The composite phase of the lithium cobalt oxide positive electrode material contains a small amount of O3 phase, which can improve the thermodynamic stability of the lithium cobalt oxide positive electrode material and realize the improvement of the discharge platform of the positive electrode, so that the lithium cobalt oxide positive electrode material of the present invention has high energy density, high thermodynamic stability and high discharge platform. The lithium cobalt oxide material of the present invention has a three-phase composite phase of O2 phase, T2 phase and O3 phase, which can obtain a higher energy density than the O3 phase. On the one hand, the O3 phase of lithium cobalt oxide is a thermodynamically stable phase with a higher discharge voltage platform, which can synergistically improve the performance of the composite phase positive electrode material, thereby increasing the energy density of the positive electrode material; on the other hand, the composite phase contains a T2 phase structure, and the introduction of the T2 phase can form LiO 4The local structure, as an interlayer "pillar", can greatly improve the structural stability of layered lithium cobalt oxide, especially the structural stability under high voltage. At the same time, by controlling the proportion of the O3 phase, the probability of irreversible phase change of the O3 phase under high charging voltage is reduced, solving the problem of material structural instability and rapid capacity decay of the O3 phase under high charging voltage. In addition, the introduction of the O3 phase into the O2 phase and T2 phase as the main phase structure to form a multi-phase composite lithium cobalt oxide positive electrode material can enrich the ion diffusion channels in the lithium cobalt oxide bulk phase structure, which is beneficial to improve the diffusion kinetics of lithium ions in the positive electrode material structure, and is beneficial to further improve the cycle stability and energy density of the lithium cobalt oxide positive electrode material under high voltage.
[0069] The present invention can synergistically exert the maximum advantages of each phase structure through the above three-phase composite and the limitation of the contents of the three phases of O2 phase, T2 phase and O3 phase: the O3 phase has higher thermodynamic stability, the T2 phase has higher thermal stability due to the presence of localized LiO 4 Stabilizing the layered material can improve the intrinsic structural stability of the material. The O2 phase has multiple ion transport paths, which can improve the material dynamics. Under high charging voltage, the O2 phase transforms into the T2 phase, which further enhances the structural stability of the lithium cobalt oxide material. By limiting the molar ratio of the three-phase structure and regulating the proportion of the composite phase in the structure, the rate performance of lithium ions in the positive electrode material, the structural stability under high voltage, the stability of the thermodynamic structure, the specific capacity, and the discharge platform can be effectively improved, thereby realizing a lithium cobalt oxide positive electrode material with excellent performance such as high energy density and high stability.
[0070] The lithium cobalt oxide positive electrode material with a composite phase of the present invention can be obtained by the following preparation method. The main steps include:
[0071] Step 110, weighing, mixing, and first sintering a sodium source and a cobalt source doped or not doped with the M1 element according to a stoichiometric ratio to obtain a P2 phase sodium cobaltate material.
[0072] Among them, the molar ratio of sodium in the sodium source to cobalt in the cobalt source is greater than or equal to 0.8; weighing according to the stoichiometric ratio is specifically: weighing according to the molar ratio of Na, Co, and M1 of [0.8-0.1]:[0.97-1]:[0-0.03].
[0073] The heating rate of the first sintering is 3-20°C / min, the sintering temperature is 700-1000°C, and the sintering time is 10-36 hours.
[0074] The cobalt source includes: one or more of cobalt tetroxide, cobalt hydroxide, cobalt chloride, cobalt acetate, cobalt sulfate, and cobalt nitrate;
[0075] The sodium source includes: one or more of sodium carbonate, sodium hydroxide, sodium chloride, sodium nitrate, and sodium sulfate;
[0076] M1 is one or more of Al, Zr, Ni, Mn, Y, Nb, La, Fe, Cu, Cr, Ti, W, Mg, Mo or Yb.
[0077] The cobalt source doped with the M1 element can be obtained from the market, or prepared by methods disclosed in the prior art, such as the metal atom doped Co 3 O 4 method.
[0078] Step 120, mixing the P2 phase sodium cobalt oxide material and the lithium source in a molar ratio of Na to Li of 1:1.5-1:10, performing a second sintering in an air atmosphere or an oxygen atmosphere to perform a molten salt ion exchange reaction, and washing the second sintered product with water to obtain a lithium cobalt oxide positive electrode material with a composite phase.
[0079] Among them, the molar ratio of Na to Li is 1:1.5-1:10, which can be written as n(Na):n(Li)=1:1.5-1:10.
[0080] The second sintering temperature rise rate is 3-20°C / min, the sintering temperature is 250°C to 300°C, and the sintering time is 12-36 hours. Preferably, the second sintering temperature rise rate is 3-15°C / min, the sintering temperature is 255°C-265°C, and the sintering time is 12-14 hours.
[0081] The lithium source includes one or more of lithium hydroxide, lithium nitrate, lithium chloride, lithium bromide, lithium sulfate, and lithium carbonate.
[0082] In this step, the lithium source is added in excess, and the sodium ions are exchanged with lithium ions through molten salt ion exchange during the reaction process. At the same time, some lithium ions may occupy certain vacancies. The exchanged sodium ions are precipitated on the surface of the material in the form of sodium salts and removed by water washing, thereby obtaining a lithium cobalt oxide positive electrode material with a composite phase.
[0083] The present invention can precisely and directionally regulate the bulk structure of lithium cobalt oxide by adjusting the sodium content in the precursor P2 phase sodium cobalt oxide and using the molten salt ion exchange method, thereby effectively controlling the lithium content in lithium cobalt oxide, so that the T2 phase structure appears and is controlled within a certain range, thereby obtaining a composite phase lithium cobalt oxide with O2 phase and T2 phase as the main phase structure and O3 phase at the same time. Since the ion exchange process may not be complete, a small amount of Na ions may exist in the bulk phase of lithium cobalt oxide.
[0084] The lithium cobalt oxide positive electrode material proposed in the present invention has high energy density, structural stability and excellent cycle performance. It can be applied to lithium batteries such as liquid lithium ion batteries, liquid metal lithium batteries, hybrid solid-liquid lithium ion batteries, hybrid solid-liquid metal lithium batteries, solid-state lithium ion batteries or solid-state metal lithium batteries. It can also be applied to lithium battery packs or lithium battery modules, and can be widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields, and also has good application prospects in large-scale energy storage systems.
[0085] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0086] Example 1
[0087] This embodiment provides a lithium cobalt oxide positive electrode material with a composite phase and a preparation process thereof.
[0088] The preparation process includes:
[0089] Step (1), Na 2 CO 3 , Al element doped Co 3 O 4 The precursor raw material mixed powder sample was obtained by mixing according to the molar ratio of n(Na):n(Co):n(Al)=0.8:1:0.02; the precursor raw material mixed powder sample was pressed into a disc with a diameter of 12 cm by a tablet press at 16 MPa, and then the disc was heated to 900°C at a heating rate of 5°C / min and sintered at high temperature for 12 hours in an oxygen atmosphere. After the reaction was completed and cooled to room temperature, Al-doped NaCoO containing a P2 phase structure was obtained. 2 Precursor;
[0090] Step (2) doping NaCoO with lithium nitrate and the Al element prepared in step (1) 2 The precursors were fully mixed at a molar ratio of n(Li):n(Na)=10:1, and the mixture was heated to 260°C at a heating rate of 5°C / min, and a molten salt ion exchange reaction was carried out in an air atmosphere for 4 hours. After the reaction was completed, it was cooled to room temperature, and the product was taken out, washed with water, and dried to obtain a lithium cobalt oxide positive electrode material with a composite phase.
[0091] After inductively coupled plasma (ICP) testing, the obtained lithium cobalt oxide positive electrode material with a composite phase has an elemental composition of Na 0.001 L i0.81 A1 0.02 Co 0.98 0 2 of positive electrode material.
[0092] Example 2
[0093] This embodiment provides a lithium cobalt oxide positive electrode material with a composite phase and a preparation process thereof.
[0094] In step (1), the molar ratio of the raw materials for preparing the precursor raw material mixed powder sample is n(Na):n(Co):n(Al)=0.85:1:0.02, and the remaining steps are the same as in Example 1.
[0095] After inductively coupled plasma (ICP) testing, the obtained lithium cobalt oxide positive electrode material with a composite phase has an elemental composition of Na 0.001 L i 0.85 A l 0.02 Co 0.98 O 2 of positive electrode material.
[0096] Example 3
[0097] This embodiment provides a lithium cobalt oxide positive electrode material with a composite phase and a preparation process thereof.
[0098] In step (1), the molar ratio of the raw materials for preparing the precursor raw material mixed powder sample is n(Na):n(Co):n(Al)=0.90:1:0.02, and the remaining steps are the same as in Example 1.
[0099] After inductively coupled plasma (ICP) testing, the obtained lithium cobalt oxide positive electrode material with a composite phase has an elemental composition of Na 0.001 L i 0.87 A l 0.02 Co 0.98 O 2 of positive electrode material.
[0100] Example 4
[0101] This embodiment provides a lithium cobalt oxide positive electrode material with a composite phase and a preparation process thereof.
[0102] In step (1), the molar ratio of the raw materials for preparing the precursor raw material mixed powder sample is n(Na):n(Co):n(Al)=1:1:0.02, and the remaining steps are the same as in Example 1.
[0103] After inductively coupled plasma (ICP) testing, the obtained lithium cobalt oxide positive electrode material with a composite phase has an elemental composition of Na 0.001 L i 0.91 A l0.02 Co 0.98 O 2 of positive electrode material.
[0104] Comparative Example 1
[0105] This comparative example provides a lithium cobalt oxide positive electrode material with a composite phase and a preparation process thereof.
[0106] In step (1), the molar ratio of the raw materials for preparing the precursor raw material mixed powder sample is n(Na):n(Co):n(Al)=0.6:1:0.02, and the remaining steps are the same as in Example 1.
[0107] After inductively coupled plasma (ICP) testing, the obtained lithium cobalt oxide positive electrode material with a composite phase has an elemental composition of Na 0.0009 Li 0.65 A l 0.02 Co 0.98 O 2 of positive electrode material.
[0108] Comparative Example 2
[0109] This comparative example provides a lithium cobalt oxide positive electrode material with a composite phase and a preparation process thereof.
[0110] In step (1), the molar ratio of the raw materials for preparing the precursor raw material mixed powder sample is n(Na):n(Co):n(Al)=0.7:1:0.02, and the remaining steps are the same as in Example 1.
[0111] After inductively coupled plasma (ICP) testing, the obtained lithium cobalt oxide positive electrode material with a composite phase has an elemental composition of Na 0.0009 Li 0.75 A l 0.02 Co 0.98 O 2 of positive electrode material.
[0112] Comparative Example 3
[0113] This comparative example provides a pure O2 phase lithium cobalt oxide positive electrode material and its preparation process.
[0114] (1) Put Na 2 CO 3 , Al element doped Co 3 O 4The precursor raw material mixed powder sample was obtained by mixing according to the molar ratio of n(Na):n(Co):n(M1)=60:90:2; the precursor raw material mixed powder sample was pressed into a disc with a diameter of 12 cm by a tablet press at 16 MPa, and then the disc was heated to 900°C at a heating rate of 5°C / min and sintered at high temperature for 12 hours in an oxygen atmosphere. After the reaction was completed and the temperature was cooled to room temperature, Al-doped Na-containing P2 phase structure was obtained. 0.7 CoO 2 Precursor;
[0115] Step (2) The Na prepared in step (1) 0.7 CoO 2 The precursor powder was placed in an aqueous solution containing lithium salt at a molar ratio of n(Li):n(Na)=10:1 and fully mixed at 100°C for 24 hours to perform hydrothermal ion exchange. After the reaction was completed, the temperature was cooled to room temperature to obtain pure O2 phase LiCoO 2 Positive electrode material.
[0116] Comparative Example 4
[0117] This comparative example provides a pure O3 phase lithium cobalt oxide positive electrode material and its preparation process.
[0118] Pure O2 phase LiCoO was prepared by the same preparation method as in Comparative Example 3. 2 The positive electrode material was used as a precursor and calcined in a muffle furnace at 600 °C for 12 hours to obtain pure O3 phase LiCoO 2 Positive electrode material.
[0119] The performance parameters of the positive electrode materials prepared in the above embodiments and comparative examples are characterized by a series of tests.
[0120] (I) Structural characterization:
[0121] The lithium cobalt oxide positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to XRD diffraction to calculate the phase composition thereof. Figure 1-2 They are the XRD test patterns of Examples 2-3, and the XRD test patterns of Examples 1 and 4 are similar thereto, with only slight differences in characteristic peak intensities. Figure 3-4 They are the XRD test diagrams of comparative examples 1-2, Figure 5 The XRD test diagram of Comparative Examples 3-4. Table 1 shows the phase composition of the positive electrode materials in various embodiments and comparative examples obtained through XRD test.
[0122] Chemical formula Phase composition Molar ratio of each phase Example 1 <![CDATA[Na 0.001 If 0.81 A1 0.02 What 0.98 0 2 ]]> O2 phase, T2 phase, O3 phase O2:T2:O3=72.28:25.9:1.82 Example 2 <![CDATA[Na 0.001 Li 0.85 Al 0.02 Co 0.98 O 2 ]]> O2 phase, T2 phase, O3 phase O2:T2:O3=46.64:47.64:5.72 Example 3 <![CDATA[Na 0.001 Li 0.87 Al 0.02 Co 0.98 O 2 ]]> O2 phase, T2 phase, O3 phase O2:T2:O3=61.58:31.71:6.71 Example 4 <![CDATA[Na 0.001 Li 0.91 Al 0.02 Co 0.98 O 2 ]]> O2 phase, T2 phase, O3 phase O2:T2:O3=42.94:47.23:9.803 Comparative Example 1 <![CDATA[Na 0.0009 Li 0.65 Al 0.02 Co 0.98 O 2 ]]> O2 phase, T2 phase O2: T2 = 1.56: 98.44 Comparative Example 2 <![CDATA[Na 0.0009 Li 0.75 Al 0.02 Co 0.98 O 2 ]]> O2 phase, T2 phase O2: T2 = 19.35: 80.65 Comparative Example 3 <![CDATA[LiCoO 2 ]]> Pure O2 phase 100% Comparative Example 4 <![CDATA[LiCoO 2 ]]> Pure O3 phase 100%
[0123] Table 1
[0124] from Figure 1 and Figure 2 It can be seen that the XRD spectrum of the lithium cobalt oxide positive electrode material with a composite phase obtained in Example 2-3 has characteristic peaks of O2, T2 and O3 phase structures at the same time, and the structural characteristics include crystal plane characteristics, that is, the prepared modified positive electrode material has the crystal plane characteristics of lithium cobalt oxide with an O2 phase structure, the crystal plane characteristics of lithium cobalt oxide with a T2 phase structure, and the crystal plane characteristics of lithium cobalt oxide with an O3 phase structure. The lithium cobalt oxide positive electrode material has two (002) characteristic diffraction peaks, one (003) characteristic peak, (112) characteristic peaks and (114) characteristic peaks, as well as one (102) characteristic peak, (105) and (104) characteristic peaks. The analysis shows that there are two (002) characteristic diffraction peaks in the O2 / T2 / O3 composite phase lithium cobalt oxide. The first (002) characteristic diffraction peak belongs to the T2 phase, with an angle of 17.00° to 18.08°; the second (002) characteristic diffraction peak belongs to the O2 phase, with an angle of 18.08° to 18.32°; the angle of the (003) characteristic diffraction peak of the O2 / T2 / O3 composite phase lithium cobalt oxide is 18.51° to 19.72°; the (112) characteristic diffraction peak of the O2 / T2 / O3 composite phase lithium cobalt oxide belongs to the T2 phase, with an angle of 40.7° to 42.2°; the (114) characteristic diffraction peak of the O2 / T2 / O3 composite phase lithium cobalt oxide belongs to the T2 phase, with an angle of 114° to 114°. The angle of the characteristic diffraction peak of lithium cobalt oxide (105) in the O2 / T2 / O3 composite phase belongs to the O2 phase, and its angle is 56.7° to 57.9°; the characteristic diffraction peak of lithium cobalt oxide (104) in the O2 / T2 / O3 composite phase belongs to the O3 phase, and its angle is 45.1° to 45.9°; the angles of the two (002) characteristic diffraction peaks in the O2 / T2 / O3 composite phase lithium cobalt oxide are smaller than the angle of the characteristic diffraction peak of the O2 single-phase lithium cobalt oxide (002) and the angle of the characteristic diffraction peak of the O3 single-phase structure lithium cobalt oxide (003).
[0125] exist Figure 1 and Figure 2In the XRD spectrum, the angles of the characteristic peaks (002), (003), (102), and (105) are all smaller than the angle of the characteristic diffraction peak (002) of O2 single-phase structure lithium cobalt oxide, the angle of the characteristic diffraction peak (003) of O3 single-phase structure lithium cobalt oxide, and the characteristic diffraction peaks (112) and (114) of T2 phase lithium cobalt oxide. In the XRD spectrum of lithium cobalt oxide of the O2 / T2 / O3 composite phase, the peak intensity of the (002) characteristic peak defined in the range of 17.00°≤2θ≤18.08° is defined as I1, the peak intensity of the (002) characteristic peak defined in the range of 18.08°≤2θ≤18.32° is defined as I2, and the peak intensity of the (003) characteristic peak defined in the range of 18.51°≤2θ≤19.72° is defined as I3, satisfying 0.5≤I2 / I1≤1.5 and 0.1≤I3 / I2≤0.8, wherein in Example 1, I2 / I1 is 0.95 and I3 / I2 is 0.34. According to an embodiment of the present invention, two (002), one (003), one (102), one (105) and one (104) as well as (114) and (112) characteristic peaks are the main characteristic peaks of the lithium cobalt oxide positive electrode material containing the O2 / T2 / O3 composite phase. The applicant has found that by adjusting the peak intensity ratio and angle of the (002) characteristic peak and the (003) characteristic peak, so that the angles of the (002) and (003) characteristic peaks are both smaller than the angle of the characteristic diffraction peak of the O2 phase lithium cobalt oxide (002) and the angle of the characteristic diffraction peak of the O3 single-phase structure lithium cobalt oxide (003), and the ratio of the intensity of the (002) and (003) characteristic diffraction peaks is within the range of 0.8≤I 2 / I 1≤1.1 and 0.2≤I 3 / I 2≤0.5, a positive electrode material with high capacity, high rate and high cycle life can be obtained.
[0126] from Figure 3 It can be seen that the XRD pattern of the lithium cobalt oxide positive electrode material obtained in Comparative Example 1 has a (002) characteristic peak corresponding to an angle of 17.00° to 18.08°, a (112) characteristic peak corresponding to an angle of 40.7° to 42.2°, and a (114) characteristic peak corresponding to an angle of 52.1° to 53.9°. The above three characteristic peaks belong to the T2 phase. In addition, there is a (002) characteristic peak corresponding to an angle of 18.08° to 18.32°, a (102) characteristic peak at an angle of 36.2° to 37.7°, and a (105) characteristic peak at an angle of 56.7° to 57.9°. The above characteristic peaks correspond to the O2 phase. Therefore, the composite phase of the positive electrode material of Comparative Example 1 is an O2 phase and a T2 phase structure. In addition, after structural analysis and fitting by Full prof software, it can be seen that the molar ratio of O2:T2 is 1.56:98.44. From Figure 4It can be seen that the XRD pattern of the lithium cobalt oxide positive electrode material obtained in Comparative Example 2 has a (002) characteristic peak corresponding to an angle of 17.00° to 18.08°, a (112) characteristic peak corresponding to an angle of 40.7° to 42.2°, and a (114) characteristic peak corresponding to an angle of 52.1° to 53.9°. The above three characteristic peaks belong to the T2 phase. In addition, there is a (002) characteristic peak corresponding to an angle of 18.08° to 18.32°, a (102) characteristic peak at an angle of 36.2° to 37.7°, and a (105) characteristic peak at 56.7° to 57.9°. The above characteristic peaks correspond to the O2 phase. Therefore, the composite phase of the positive electrode material of Comparative Example 2 is an O2 phase and a T2 phase structure. In addition, after structural analysis and fitting by Full prof software, it can be seen that the molar ratio of O2:T2 is 19.35:80.65.
[0127] It can be seen from Table 1 that when the molar ratio of sodium to cobalt in the precursor is less than 0.8, there is no O3 phase in the composite phase, and when the molar ratio of sodium to cobalt is greater than or equal to 0.8, there will be a certain proportion of O3 phase. It can be seen from Comparative Examples 1-2 that as the sodium content in the precursor increases, the proportion of T2 phase structure in the composite phase structure decreases, while the proportion of O2 phase increases. When the ratio of sodium to cobalt increases from 0.6 to 0.7, the molar ratio of T2 phase structure decreases by about 18%. This is because when the sodium atom content in the precursor is high, lithium ions can replace interlayer sodium sites during the ion exchange process to form O2 phases. As the Na content in the precursor increases, it can be replaced by more Li ions during the ion exchange process, which helps Li occupy the octahedral sites of the alkali metal layer to form more O2 phases. It can be seen from Examples 2-3 that as the sodium content in the precursor increases, the proportion of O2 and O3 phase structures in the composite phase structure increases, while the proportion of T2 phase decreases. This is because a small amount of metastable phase may exist in the sodium-rich precursor and may promote phase transformation to O3 phase during the ion exchange process.
[0128] like Figure 5 As shown, by heating, the O2 phase lithium cobalt oxide (P63mc) in Comparative Example 3 is transformed into the O3 phase lithium cobalt oxide of the R-3m space group shown in Comparative Example 4, and it can be seen that O3 has a (003) characteristic peak and a (104) characteristic peak with an angle of 45.1° to 45.9°, as well as characteristic diffraction peaks after 50 degrees, such as a (105) characteristic peak with an angle of 49.0° to 50.3°, a (110) characteristic peak with an angle of 66.1° to 67.3°, and a (113) characteristic peak with an angle of 69.1° to 70.6°.
[0129] (II) Morphological characterization:
[0130] The morphology of the materials obtained in the examples and comparative examples was characterized by SEM test:
[0131] Figures 6 to 13 The SEM images of the positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-4 respectively. It can be seen that the positive electrode materials in Examples 1-4 and Comparative Examples 1-4 all present a flake-like morphology with a particle size of 5-30 μm. Fig.12 and Fig.13 By comparison, it can be seen that after calcination, the O2 phase material is transformed into the O3 phase material, and its morphological characteristics do not change, only the structural phase change occurs.
[0132] (III) Electrochemical performance test:
[0133] Electrochemical tests were performed on each embodiment and comparative example, and button-type half-cells for testing were made using the positive electrode materials prepared in each embodiment and comparative example. The specific production steps are as follows.
[0134] The positive electrode materials of each embodiment and comparative example are used to prepare positive electrode sheets of lithium-ion batteries:
[0135] The positive electrode material was mixed with the conductive additive Super P and the binder polyvinylidene fluoride in a mass ratio of 8:1:1, and an appropriate amount of organic solvent N-methylpyrrolidone was added to form a uniformly dispersed slurry. Then, it was evenly coated on the aluminum foil current collector with a scraper and placed in an oven for drying. The dried electrode sheet was punched to obtain an active material loading of about 2.5 mg / cm 2 The positive electrode sheet.
[0136] Assemble the lithium-ion button cell:
[0137] The prepared positive electrode sheet and the metal lithium negative electrode sheet were assembled into a lithium-ion button battery in a glove box filled with argon gas and with a water and oxygen content of less than 0.1 ppm.
[0138] The assembled button cells were subjected to electrochemical charge and discharge tests at a test voltage range of 3-4.6 V. The cycle performance test was first performed at a current density of 0.1 C (1 C = 270 mA / g) for two weeks, and then a charge and discharge cycle test was performed at 0.5 C. The test results are shown in Table 2. The charge and discharge cycle curves of Examples 1-4 and Comparative Examples 1-4 are shown in Table 2. Figure 14-21 shown.
[0139]
[0140]
[0141] Table 2
[0142] The first discharge specific capacity at 0.1C and 0.5C, the energy density at 0.5C, and the energy density after 100 cycles at 0.5C of the batteries assembled with the positive electrode materials of Examples 1-4 and the positive electrode materials of Comparative Examples 1-4 are recorded in Table 2, respectively.
[0143] From the perspective of the first discharge specific capacity at 0.1C and 0.5C and the energy density at 0.5C, Examples 1-4 are superior to Comparative Examples 1-4. Since Examples 1-4 are composite phases of O2 phase, T2 phase and O3 phase, they can synergistically exert the maximum advantages of each phase structure. The O3 phase has higher thermodynamic stability, and the T2 phase has a high thermal stability due to the presence of localized LiO 4 Stabilizing the layered material can improve the intrinsic structural stability of the material. The O2 phase has multiple ion transport paths, which can improve the material dynamics. The O2 phase transforms into the T2 phase at a high charging voltage to improve the structural stability of the material. The discharge platform of the positive electrode material can be improved through the synergistic effect of the three phases, thereby improving the energy density of the composite material.
[0144] From the results of various performance tests, Examples 2-4 are better than Example 1, because the ratio of T2 phase to O3 phase in the bulk structure is increased. The increase in the ratio of O3 phase can ensure that the battery has a higher specific capacity and energy density, and the increase in the ratio of T2 phase can be beneficial to the structural stability under high voltage.
[0145] Among them, the positive electrode materials of Examples 3 and 4 have the highest specific capacity at 0.5C and have very high energy density. In Example 3, the proportion of O3 reaches 6.71%, and in Example 4, the proportion of O3 reaches 9.803%. This shows that the introduction of a certain content of O3 phase can improve the energy density of the positive electrode material. The positive electrode material of Example 2 is also a three-phase composite structure, and O2: T2: O3 = 46.64: 47.64: 5.72. Among them, the O3 phase ratio is reduced by 0.99% relative to Example 3, so its energy density is 894Wh / kg, which is slightly lower than that of Example 3 (898Wh / kg), but after 100 cycles at 0.5C, the energy density of the positive electrode material of Example 2 is 24Wh / kg higher than that of Example 3, showing better performance under high voltage. The difference between Examples 2 and 3 is that there are relatively more O3 structures in the bulk structure of Example 3, which will bring greater structural stress to the overall structure of the material under high voltage, thereby causing the material to be slightly less stable during the cycle. Therefore, an appropriate content of O3 phase structure can improve the overall capacity and energy density of the positive electrode material. Even when cycling at high voltage, the structural stress in some local structures caused by the phase change of the appropriate amount of O3 phase in the positive electrode material under high voltage will not cause irreversible effects on the overall structural stability of the positive electrode material.
[0146] The composite phases of the positive electrode materials of Comparative Examples 1-2 are O2 phase and T2 phase, and the O2 phase content in Comparative Example 2 is higher than that in Comparative Example 1, while the T2 phase content is lower than that in Comparative Example 1. From the perspective of the first discharge specific capacity at 0.1C and 0.5C, the energy density at 0.5C, and the energy density after 100 cycles at 0.5C, Comparative Example 2 is higher than Comparative Example 1. This is because the sodium content in the precursor used in Comparative Example 2 is higher than that in the precursor in Comparative Example 1, resulting in the positive electrode material of Comparative Example 2 having a higher lithium content after ion exchange. Therefore, during the first discharge process, Comparative Example 2 has a higher discharge capacity than Comparative Example 1, but both fail to reach the performance of Examples 1-4.
[0147] From the perspective of the first discharge capacity at 0.1C, Comparative Examples 1-2 are lower than Comparative Examples 3-4, but from the perspective of the first discharge capacity at 0.5C and the energy density after 100 cycles at 0.5C, Comparative Examples 1-2 are higher than Comparative Examples 3-4; and from the perspective of the energy density at 0.5C, Comparative Examples 1-2 are higher than Comparative Example 3 and similar to Comparative Example 4. Since Comparative Examples 1-2 are composite phases of O2 phase and T2 phase, Comparative Example 3 is a pure O2 phase of LiCoO 2 , Comparative Example 4 is pure O3 phase LiCoO 2 Since the initial structure of Comparative Example 1-2 is in a lithium-deficient state, the initial discharge capacity of Comparative Example 1-2 is lower than that of the fully lithium-state O2 phase LiCoO at 0.1C. 2 After activation at 0.1C, Comparative Examples 1-2 showed a significant improvement compared to pure O3 phase LiCoO 2 Higher energy density and capacity retention rate, this is because the T2 phase with a larger interlayer spacing in the initial structure of Comparative Example 1-2 can store more lithium ions, and combined with the structural stability of the O2 phase, the structural reversibility of the composite phase structure during the charge and discharge process is improved. It is worth noting that after the initial activation and complete lithium replenishment, the lithium-deficient state in Comparative Example 1-2 disappears, and its electrochemical behavior is similar to that of the pure O2 phase Li CoO in Comparative Example 3. 2 Consistent.
[0148] Fig. 22The energy density comparison chart of lithium-ion batteries assembled from positive electrode materials of Examples 2-3 and Comparative Examples 1-4 after 100 cycles at a current density of 0.5C. By converting the corresponding energy density with the discharge voltage platform and the discharge specific capacity after 100 cycles, it can be seen that after 100 cycles, Examples 2-3 have higher energy density and better performance than Comparative Examples 1-4. In Examples 2-3, as the specific capacity of the material is improved with the increase of the O3 phase structure in the composite phase structure, the examples have higher energy density after 100 cycles at a current density of 0.5C. The embodiments of the present invention have better cycle performance. This is because the O2 and T2 phases in the composite phase will transform into each other during the charge and discharge process as the interlayer Li ion concentration changes. Due to the presence of LiO in the T2 phase 4 Local configuration, and LiO 4 It can be used as an interlayer pillar to stabilize the laminate structure. The presence of two lithium ion diffusion channels in the O2 phase structure can improve the material kinetics. It is worth noting that the cycle stability of the composite phase structure positive electrode material is higher than that of the pure O2 and O3 phase positive electrode materials. However, the thermodynamic metastability characteristics of the O2 and T2 phases determine that their electrode reaction potential is lower than that of the structurally thermodynamically stable O3 phase. Therefore, by comparing the embodiments and comparative examples, introducing an appropriate content of O3 phase structure into the lithium cobalt oxide positive electrode material composite of O2 and T2 phases can effectively improve the energy density of the positive electrode material.
[0149] Tables 3 and 4 are rate performance tests of constant current and constant voltage charging and constant current discharging of Examples 1-4 and Comparative Examples 1-4 at 25°C, in the range of 3-4.6V, with currents of 0.1C, 0.5C, 1C, 2C, and 5C, respectively, for 5 cycles. Fig.23 The figure is a rate performance diagram of lithium-ion batteries assembled from the positive electrode materials of Examples 1-4 and Comparative Examples 1-4 at current densities of 0.1C, 0.5C, 1C, 2C, 3C, and 5C.
[0150] The test results of Examples 1-4 are shown in Table 3.
[0151]
[0152] Table 3
[0153] The test results of Comparative Examples 1-4 are shown in Table 4.
[0154]
[0155]
[0156] Table 4
[0157] By comparison, it can be seen that when the current density is increased, the difference in discharge specific capacity between the embodiment and the comparative example gradually emerges. Especially relative to the pure O2 phase and the pure O3 phase, it has better rate performance. Especially at a current density of 10C, embodiments 1-4 still maintain good performance, and the specific capacity is higher than 160mAh / g, but the capacity retention rate of comparative examples 1-4 drops below 80%, especially the positive electrode materials of comparative examples 3-4, the specific capacity is lower than 100mAh / g, almost completely attenuated, and the specific capacity of comparative example 1-2 is also relatively low.
[0158] Because there is LiO in the T2 phase of the composite phase structure 6 Octahedron and CoO 6 The local structural environment of the tetrahedral interstitial sites formed by the coplanar octahedrons allows Li ions to diffuse quickly between layers through the tetrahedral interstitial sites, ensuring a high ion diffusion rate of the positive electrode material at high current density. The special oxygen stacking method of the O2 phase improves the mechanical stability of the material. Under high current density, the presence of a moderate O3 phase can improve the overall discharge platform and energy density of the positive electrode material, while excessive O3 phase content, such as pure O3 phase, may cause structural failure under high voltage and high rate conditions, such as irreversible structural phase change and lattice oxygen escape, which will eventually lead to a decrease in the material capacity retention rate, so the proportion of the O3 phase needs to be reasonably regulated. Under the 10C high current density test conditions, the discharge specific capacity and capacity retention rate of the positive electrode materials of Examples 1-4 are higher than those of the positive electrode materials of Comparative Examples 1-4. It can be shown that the positive electrode material with a composite phase structure of the present invention has excellent rate performance.
[0159] It can be seen from the above electrochemical test results that the lithium cobalt oxide positive electrode material containing a composite structure of O2, T2 and O3 phases prepared by the molten salt ion exchange method in the present application is not only simple in preparation method and easy to scale up, but also has obvious advantages in electrochemical performance compared to pure phase lithium cobalt oxide and lithium cobalt oxide with only a composite structure of O2 and T2 phases.
[0160] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A lithium cobalt oxide positive electrode material having a composite phase, characterized in that: The chemical formula of the lithium cobalt oxide positive electrode material having a composite phase is A X Co 1-y M1 y O2; Wherein, 0.5≤x≤1, 0≤y≤0.03, A is Li or Li and Na, and M1 is one or more of Al, Zr, Ni, Mn, Y, Nb, La, Fe, Cu, Cr, Ti, W, Mg, Mo or Yb; The composite phase of the lithium cobalt oxide positive electrode material includes an O2 phase, a T2 phase and an O3 phase; wherein the sum of the molar proportions of the O2 phase and the T2 phase in the composite phase is greater than or equal to 90%, and the molar proportion of the O3 phase is greater than 0 and less than or equal to 10%.
2. The lithium cobalt oxide positive electrode material with a composite phase according to claim 1, characterized in that: The chemical formula of the lithium cobalt oxide positive electrode material having a composite phase is Li x1 Na X2 Co 1-y M1 y O2, 0.5<x1<0.996, 0.0001≤x2≤0.004, 0≤y≤0.03, M1 is at least one of Al, Mg, and Ti.
3. The lithium cobalt oxide positive electrode material with a composite phase according to claim 1, characterized in that: The molar ratio of the O2 phase in the composite phase is 1%-65%, the molar ratio of the T2 phase in the composite phase is 25%-98%, and the molar ratio of the O3 phase in the composite phase is 1%-10%.
4. The lithium cobalt oxide positive electrode material with a composite phase according to claim 3, characterized in that: The O2 phase, the T2 phase and the O3 phase are evenly or unevenly distributed in the bulk structure of the lithium cobalt oxide positive electrode material; The molar ratio of the O2 phase in the composite phase is 40%-65%, the molar ratio of the T2 phase in the composite phase is 30%-55%, and the molar ratio of the O3 phase in the composite phase is 5%-10%.
5. The lithium cobalt oxide positive electrode material with a composite phase according to claim 1, characterized in that: M1 is evenly distributed or gradiently distributed in the bulk phase of the lithium cobalt oxide positive electrode material having a composite phase.
6. The lithium cobalt oxide positive electrode material with a composite phase according to claim 1, characterized in that: Lithium cobalt oxide with T2 phase structure has a characteristic peak corresponding to the (002) crystal plane in the range of 17.00°≤2θ≤18.08°, a characteristic peak corresponding to the (112) crystal plane in the range of 40.7°≤2θ≤42.2°, and a characteristic peak corresponding to the (114) crystal plane in the range of 52.1°≤2θ≤53.9°; Lithium cobalt oxide with O2 phase structure has a characteristic peak corresponding to the (002) crystal plane in the range of 18.08°<2θ≤18.32°, a characteristic peak corresponding to the (102) crystal plane in the range of 36.2°≤2θ≤37.7°, and a characteristic peak corresponding to the (105) crystal plane in the range of 56.7°≤2θ≤57.9°; Lithium cobalt oxide with O3 phase structure has a characteristic peak corresponding to the (003) crystal plane in the range of 18.51°≤2θ≤19.72°, and a characteristic peak corresponding to the (104) crystal plane in the range of 45.1°≤2θ≤45.9°; Among them, the characteristic peak intensity of the T2 phase structure corresponding to the (002) crystal plane in the range of 17.00°≤2θ≤18.08° is I1, the characteristic peak intensity of the O2 phase structure corresponding to the (002) crystal plane in the range of 18.08°<2θ≤18.32° is I2, and the characteristic peak intensity of the O3 phase structure corresponding to the (003) crystal plane in the range of 18.51°≤2θ≤19.72° is I3, I1, I2, and I3 satisfy 0.5≤I2 / I1≤1.5, 0.1≤I3 / I2≤0.8; preferably, 0.8≤I2 / I1≤1.1, 0.2≤I3 / I2≤0.
5.
7. The lithium cobalt oxide positive electrode material with a composite phase according to claim 1, characterized in that: The lithium cobalt oxide positive electrode material with a composite phase is a spherical particle composed of primary particles and / or secondary particles; The primary particles are composed of one or more crystal grains, the primary particles are flaky in shape, and have an average particle size of 4 μm-50 μm, preferably 5 μm-30 μm; the secondary particles are composed of agglomerates of multiple primary particles.
8. A method for preparing a lithium cobalt oxide positive electrode material having a composite phase as claimed in any one of claims 1 to 7, characterized in that: The method comprises: The sodium source and the cobalt source doped or not doped with the M1 element are weighed, mixed, and first sintered according to a stoichiometric ratio to obtain a P2 phase sodium cobaltate material; wherein the molar ratio of sodium in the sodium source to cobalt in the cobalt source is greater than or equal to 0.8; the first sintering has a heating rate of 3-20°C / min, a sintering temperature of 700-1000°C, and a sintering time of 10-36 hours; The P2 phase sodium cobalt oxide material is mixed with a lithium source in a molar ratio of n(Na):n(Li)=1:1.5-1:10, and a second sintering is performed in an air atmosphere or an oxygen atmosphere to carry out a molten salt ion exchange reaction, and the second sintered product is washed with water to obtain a lithium cobalt oxide positive electrode material with a composite phase; wherein the heating rate of the second sintering is 3-20°C / min, the sintering temperature is 250°C to 300°C, and the sintering time is 12-36 hours.
9. The preparation method according to claim 8, characterized in that: The cobalt source includes: one or more of cobalt tetroxide, cobalt hydroxide, cobalt chloride, cobalt acetate, cobalt sulfate, and cobalt nitrate; The sodium source includes: one or more of sodium carbonate, sodium hydroxide, sodium chloride, sodium nitrate, and sodium sulfate; M1 is one or more of Al, Zr, Ni, Mn, Y, Nb, La, Fe, Cu, Cr, Ti, W, Mg, Mo or Yb; The weighing according to the stoichiometric ratio is specifically: weighing according to the molar ratio of Na, Co, and M1 being [0.8-1]: [0.97-1]: [0-0.03]; The lithium source includes: one or more of lithium hydroxide, lithium nitrate, lithium chloride, lithium bromide, lithium sulfate, and lithium carbonate; The heating rate of the second sintering is 3-15°C / min, the sintering temperature is 255°C-265°C, and the sintering time is 12-14 hours.
10. A lithium battery, characterized in that: The lithium battery comprises the lithium cobalt oxide positive electrode material with a composite phase as described in any one of claims 1 to 7 above, or comprises the lithium cobalt oxide positive electrode material with a composite phase prepared by the preparation method described in claim 8 or 9 above; The lithium battery includes any one of a liquid lithium ion battery, a liquid metal lithium battery, a hybrid solid-liquid lithium ion battery, a hybrid solid-liquid metal lithium battery, a solid lithium ion battery or a solid metal lithium battery.
Citation Information
Patent Citations
Modified positive electrode material and battery containing same
CN117374271A
Composite positive electrode material, preparation method thereof and battery
CN118693253A
Lithium cobalt oxide material and preparation method and application thereof
CN118712376A
Cobalt-Based Lithium Metal Oxide Cathode Material
US20180190976A1
Cited By
Composite-phase core-shell lithium cobalt oxide as well as preparation method and application thereof
CN121054649A
Positive electrode material and preparation method thereof, positive electrode plate and battery
CN121054690A
O2-lithium cobalt oxide material, preparation method thereof and lithium ion battery
CN121426186A
Positive electrode material, electrochemical device, and electronic device
WO2026174429A1
Positive electrode material, secondary battery, and electronic device
WO2026178688A1
